Manual lymphatic drainage and Kinesio taping applications reduce early-stage lower extremity edema and pain following total knee arthroplasty - Guney-Deniz, Hande; Kinikli, Gizem Irem; Aykar, Sercan; Sevinc, Ceyda; Caglar, Omur; Atilla, Bulent; Yuksel, Inci (Physiotherapy theory and practice, 2023)
Controlling early symptoms following total knee arthroplasty (TKA) is critical for long-term outcomes. The purpose of this study was to compare the efficacy of manual lymphatic drainage (MLD) and Kinesio Taping®(KT) applications in terms of reducing lower extremity edema, pain, and improving function in the early postoperative period of TKA. Forty-five female patients with unilateral TKA were allocated to an additional postoperative MLD treatment (n = 15) with exercises, additional Kinesio Taping® (n = 15) with exercises, or exercise-only (n = 15). Lower limb circumference, range of motion (ROM), pain level, and knee osteoarthritis outcome score (KOOS) were compared. Both MLD (p < .001; effect size range = 0.65-0.87) and the KT group (p = .001; effect size range = 0.74-0.78) had lower edema and pain levels (MLD group: p < .001; effect size = 0.84; KT group: p < .001; effect size = 0.78) compared to the control group on postoperative day 4. These beneficial effects continued only two weeks postoperatively, and no group differences were found by six weeks. Additional MLD or KT applications to standard exercises were both effective on early-stage lower extremity edema and pain levels. Clinicians might implement one of these applications to the standard rehabilitation programs to control pain and edema following TKA.